Development of fiber-rich cake based on mocaf and hunkwe flour for hypercholesterolemia prevention - Mujayanah, Ani Rosa Putri Ayu; Kurniawati, Fitria (Institute of Computer Science (IOCS), 2025)
Hypercholesterolemia is a metabolic disorder characterized by high blood cholesterol levels and is often associated with low fiber intake. In Indonesia, the prevalence of hypercholesterolemia remains concerning, affecting approximately 30% of the population and increasing with age. One way to prevent this condition is to increase the consumption of high-fiber foods. Sponge cake made from mocaf and hunkwe flour is an alternative in the development of functional food products based on local ingredients. Mocaf and hunkwe flour contain high fiber, especially water-soluble fiber, which can help lower cholesterol levels through the mechanism of binding bile acids, increasing lipid excretion, and inhibiting fat absorption in the intestine. This research was conducted using a randomized block design (RBD) with a single factor and six different treatment combinations of mocaf flour and hunkwe rations (90:10, 80:20, 70:30, 60:40, 50:50, and 40:60), each with four replications. Fiber content was analyzed using an enzymatic-gravimetric method and statistically tested using ANOVA and DMRT. The findings indicated treatments had a significant difference (p < 0.05). The largest amount of fiber content was found in the 40:60 formulation ratio (5.83%), and the smallest was in the 90:10 ratio (4.83%). The results imply that a greater percentage of hunkwe flour increases the fiber content in the final product. This formulation shows potential for development into a functional food that helps prevent hypercholesterolemia.